2018
DOI: 10.1111/gfs.12396
|View full text |Cite
|
Sign up to set email alerts
|

Silage additives to reduce protein degradation during ensiling and evaluation of in vitro ruminal nitrogen degradability

Abstract: Despite the high degradability of their proteins, grass and legume silages represent an important option to reach more sustainable livestock systems. To improve the nitrogen use efficiency of these crops, this study assessed the potential of several additives (chestnut tannins, oak tannins, zeolite, erythritol by‐product solution and wood molasses) to reduce proteolysis in the silo and in vitro nitrogen degradability. Ryegrass (Lolium multiflorum) and red clover (Trifolium pratense) were ensiled in varying pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 38 publications
7
22
0
1
Order By: Relevance
“…In the present study, all the silages had relative low protein solubility in the borate-phosphate buffer, where UC-S and CA-S had increased (P <0.05) soluble crude protein, inferring that uncompacted silage suffered more severe proteolysis, given its high NPN concentration, and the addition of citrate caused more protein acidolysis. The low protein solubility may be because of the high tannin content (condensed tannin>7%), because tannin extracts are able to bind with proteins to form complexes and prevent protein hydrolysis in silage and in the rumen (Piluzza et al, 2014;Herremans et al, 2019). It was reported that naturally occurring condensed tannins contributed to the reduced proteolysis of alfalfa during conservation (Grabber & Coblentz, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, all the silages had relative low protein solubility in the borate-phosphate buffer, where UC-S and CA-S had increased (P <0.05) soluble crude protein, inferring that uncompacted silage suffered more severe proteolysis, given its high NPN concentration, and the addition of citrate caused more protein acidolysis. The low protein solubility may be because of the high tannin content (condensed tannin>7%), because tannin extracts are able to bind with proteins to form complexes and prevent protein hydrolysis in silage and in the rumen (Piluzza et al, 2014;Herremans et al, 2019). It was reported that naturally occurring condensed tannins contributed to the reduced proteolysis of alfalfa during conservation (Grabber & Coblentz, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…La concentración de nitrógeno amoniacal en los ensilados se incrementó con la inclusión de nopal y nopal fermentado (P<0.05, tabla 3). Este incremento registrado en los ensilados del t2 y t3 pudo haber sido ocasionado por un aumento en los microorganismos que degradan proteína (Berumen et al, 2015;Ruangyote y Metha, 2018), o también el empleo de rastrojo de maíz reduce la cantidad de carbohidratos solubles y por lo tanto aumenta la degradación de proteínas (Herremans et al, 2019). Sin embargo, para clasificar un ensilado como de buena calidad, la concentración de nitrógeno amoniacal máxima debe ser de 7-20 % del nitrógeno total (Sánchez y García, 2017); por lo cual los ensilados experimentales obtuvieron valores que se encuentran dentro de este rango y por lo tanto indican que se llevó a cabo un adecuado proceso de fermentación.…”
Section: Resultados Y Discusión Composición Químicaunclassified
“…In a study comparing the effects of tannin levels in sorghum silages supplemented or not with tannin-inactivating polyethylene glycol (PEG), silages without PEG had higher protein levels and lower NH 3 concentrations than silages with PEG [26]. Tannins can also be successfully supplemented in silage via byproducts (e.g., green tea waste, [27] and plant extracts containing hydrolysable tannins from chestnut and oak [28,29] or condensed tannins from quebracho [30].…”
Section: Improving Silage Qualitymentioning
confidence: 99%
“…Other PBC including erythritol byproduct solution and lignosulphonates from wood molasses were studied as silage additives to reduce in-silo proteolysis but were shown to be less efficient compared to tannin solutions [29]. In contrast, spraying essential oils (eugenol, thymol, cinnamaldehyde and carvacrol) before ensiling ryegrass was shown to reduce protein degradation, but usually had to be sprayed at a concentration of 2 g/kg fresh forage to observe inhibition of amino acid deamination [34].…”
Section: Improving Silage Qualitymentioning
confidence: 99%